Contribution of cryptic epitopes in designing a group A streptococcal vaccine. Issue 8 (3rd August 2018) - Ozberk, Victoria; Pandey, Manisha; Good, Michael F.
ABSTRACT: A successful vaccine needs to target multiple strains of an organism. Streptococcus pyogenes is an organism that utilizes antigenic strain variation as a successful defence mechanism to circumvent the host immune response. Despite numerous efforts, there is currently no vaccine available for this organism. Here we review and discuss the significant obstacles to vaccine development, with a focus on how cryptic epitopes may provide a strategy to circumvent the obstacles of antigenic variation.